Język w modelowaniu relacji dziecko–dorosły w tekstach popularnonaukowych dla najmłodszych - Bortliczek, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article is composed of four parts where the linguistic manners of marking a sender’s and an addressee’s occurrence are analyzed. The following aspects of narrations are described in the subsequent parts of the draft such as defining in an accessible way, developing an illusion of conversation, implementing colloquial metaphors (to expose the vividness of the discourse). There is also an avoidance of learning asymmetry between a sender (a popularizer of knowledge) and an addressee with the help of small number of terms and open manner of their explanation as well as adherence to the verbal etiquette and simultaneous implementation of the direct expressions for the addressee. To summarize, senders of the scientific texts for children pay attention, among others, to the realization of such language features as the accessibility, vividness and dialogue.